Study of Rasm Al-Qur'an: Rasm Analysis of Surah Yasin in the Manuscript of Al-Qur'an Kaji Ngali Badongan, Semin, Gunungkidul - Andika Lindra Widyaningsih,; Khairun Niam, (Journal of Islamic History and Manuscript, 2024)
This article examines the Mushaf Al-Qur'an Kaji Ngali Badongan Gunugkidul, Yogyakarta. This privately owned manuscript is kept by Nur Yahman, the manuscript's heir. Historically, the manuscript has two different sources regarding its first copyist. The research focuses on the analysis of the rasm in surah Yasin contained in the Kaji Ngali Badongan manuscript. The method used is content analysis with text analysis and philology with the approach of codicology and textology. The final result of this research shows that the manuscript of Kaji Ngali Badongan Al-Qur'an Mushaf uses simple geometric illumination located at the beginning and middle of the Mushaf. The rasm ilma'i is still applied in the rule of ḥadf al-alif, besides that the rasm used is rasm usmani and Imla'i. Corrupt or unavoidable writing errors include, corrected errors, repeated writing, and lack of verse composition